RAISING LEGAL AWARENESS AND LEGAL CULTURE - AN IMPORTANT CONDITION FOR ENSURING THE RULE OF LAW (Modern education and development, 2025)
The article discusses the measures being taken in the Republic of Uzbekistan to improve the legal awareness and legal culture of the population, to increase the level of legal literacy of citizens in society, and the significance of the Decree of our President “On radically improving the system for improving legal awareness and legal culture in society” in this regard.